Pengembangan Masyarakat Melalui KKN Merdeka Belajar Dalam Pengembangan Kemandirian di Tengah Pandemi Covid 19 Distrik Warmare Kabupaten Manokwari: Community Development Through Independent Learn KKN in The Middle Of Pandemi Covid 19 in Warmare District, Manokwari Regency - Yustina L. D. Wambrauw; Lukas Y. Sonbait; Mulyadi Mulyadi (Fakultas Peternakan Universitas Papua, 2020)
ABSTRACT Community Service Program (KKN) is a manifestation of the Papua University Higher Education, namely community service. Community service is a form of knowledge that is expressed theoretically in college to be applied in real life in the Dindey village community, so that the knowledge gained can be applied and developed in the life of the wider community. In general, the objectives to be achieved from independent learning KKN are; Train and instill personality values, change the perspective, mindset and attitudes, behavior and work methods of both students and society in solving problems in society, raising awareness and building an optimistic attitude, enhancing Indonesia that is sovereign, independent and has personality. Raise public awareness about health protocols in the midst of a pandemic. Developing the independence of students and society in the midst of the COVID-19 pandemic. Kampung Dindey is one of the areas targeted for KKN-PPM activities in providing religious, education, health, environmental, agricultural and village administration assistance. Through this activity, it is hoped that the implementation of teaching reading and writing to eradicate illiteracy, so that there will be a decrease in illiteracy, especially in Manokwari Regency and public awareness of the importance of protecting yourself from the corona virus pandemic. In general, all programs can be absorbed thanks to the support of the local government. Constraints that are still encountered are the low level of community participation in several activities and the low independence of the target groups. Hopefully in the future to be used as a model, the assistance of programs that have been formed must be continued through the next Community Service Program. Keywords: Freedom community service; independence; covid pandemic 19. ABSTRAK Kuliah Kerja Nyata (KKN) merupakan salah satu perwujudan dari Perguruan Tinggi Universitas Papua yaitu pengabdian pada masyarakat. Pengabdian merupakan suatu wujud dari ilmu yang tertuang secara teoritis di bangku kuliah untuk diterapkan secara nyata dalam kehidupan sehari-hari di masyarakat kampung Dindey ini, sehingga ilmu yang diperoleh dapat diaplikasikan dan dikembangkan dalam kehidupan masyarakat luas. Tujuan dari KKN merdeka belajar adalah melatih dan menanamkan nilai kepribadian, mengubah cara pandang, pola pikir dan sikap, perilaku dan cara kerja baik mahasiswa maupun masyarakat dalam menyelesaikan permasalahan yang ada di masyarakat, membangkitkan kesadaran dan membangun sikap optimis, meningkatkan Indonesia yang berdaulat, berdikari dan berkepribadian. Meningkatkan kesadaran masyarakat tentang protokol kesehatan di tengah pandemi. Mengembangkan kemandirian diri mahasiswa dan masyarakat di tengah pandemi COVID-19. Kampung Dindey ini merupakan salah satu daerah yang dijadikan target kegiatan KKN-PPM dalam melakukan pendampingan keagaamaan, pendidikan, kesehatan, lingkungan, pertanian dan administrasi kampung. Melalui kegiatan ini diharapkan terjadi pelaksanaan pengajaran membaca dan menulis untuk pemberantasan buta aksara, sehingga terjadi penurunan buta aksara khususnya di Kabupaten Manokwari serta kesadaran masyarakat tentang pentingnya melindungi diri dari pandemi virus corona. Secara umum seluruh program bisa terserap berkat dukungan dari pemerintah daerah. Kendala yang masih ditemui adalah masih rendahnya partisipasi masyarakat di beberapa kegiatan, serta masih rendahnya kemandirian pada kelompok sasaran. Harapannya bisa dijadikan model, maka pendampingan program yang sudah terbentuk harus dilanjutkan melalui KKN berikutnya. Kata Kunci: KKN merdeka; kemandirian; pandemi covid 19.